Students' Perceptions of a Blended Learning Environment to Promote Critical Thinking - Lu, Dan (Frontiers in Psychology, 2021)
Critical thinking is considered as one of the indispensable skills that must be possessed by the citizens of modern society, and its cultivation with blended learning has drawn much attention from researchers and practitioners. This study proposed the construction of a blended learning environment, where the pedagogical, social, and technical design was directed to fostering critical thinking. The purpose of the study was to find out students’ perceptions of the learning environment concerning its design and its influence on their critical thinking. Adopting the mixed method, the study used questionnaire and interview as the instruments for data collection. The analysis of the data revealed that the students generally held positive perceptions of the environment, and they believed that the blended learning environment could help promote their critical thinking in different aspects.